E-Arsip UKM Paskamras Berbasis Web Menggunakan Framework Laravel - Putra, Christovan Hosyan Ananta; Soni, A.A.; Sudandi, I Gede Agus; Candra, I Kadek Agus Surya; Mahesa, I Gusti Made Wahyu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a web-based E-Archive system for the PASKAMRAS Student Activity Unit (UKM) using the Laravel framework. The system developed is expected to facilitate digital archive management, increase efficiency in searching and managing data, and reduce the risk of losing important documents that usually occurs in manual archive systems. The system development process goes through the stages of data collection, needs analysis, design, implementation, and testing. The main features that were successfully implemented include document management, archive search systems, and archive data reporting. System testing shows that this application can operate well, meet user needs, and is effective in supporting student organization administration. The results of this study indicate that the use of web-based technology, especially the Laravel framework, is an efficient and effective solution in managing electronic archives, and can be adapted to the needs of other student organizations.